1987
DOI: 10.1113/jphysiol.1987.sp016445
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the human diaphragm from the motor cortex.

Abstract: SUMMARY1. Rapidly conducting corticofugal pathways were activated by percutaneous electrical stimulation of the motor cortex in normal subjects. The electromyographic response produced in the diaphragm was assessed with. recordings via a gastrooesophageal catheter and the mechanical response was measured as a change in transdiaphragmatic pressure.2. The mean latency from the cortical stimulus to the muscle action potential in the diaphragm was 12-3 ms. The latency to the diaphragm from stimulation of the cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(143 citation statements)
references
References 23 publications
10
126
6
Order By: Relevance
“…However, the mean value of Cx-MEP latency of our patients was slightly longer with respect to controls. Our Cx-MEP latency values from Dia are comparable with those reported by Gandevia and Rothwell (1987) and Zifko et al (1996), although 1.5 ms longer than those reported by Khedr and Trakhan (2001). Such a discrepancy can be due to methodological differences with regard to the site of cortical stimulation and of the recording electrodes.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the mean value of Cx-MEP latency of our patients was slightly longer with respect to controls. Our Cx-MEP latency values from Dia are comparable with those reported by Gandevia and Rothwell (1987) and Zifko et al (1996), although 1.5 ms longer than those reported by Khedr and Trakhan (2001). Such a discrepancy can be due to methodological differences with regard to the site of cortical stimulation and of the recording electrodes.…”
Section: Discussionsupporting
confidence: 71%
“…The study by Corfield et al (1998) demonstrated that motor cortical excitation of the diaphragm is not mediated via brainstem respiratory neurons but, most likely, via the more direct corticospinal tract, fast conducting and oligosynaptic (Gandevia and Rothwell, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical representation of the diaphragm within the primary motor cortex was first detected using cortical electrical stimulation by Foerster in 1936 [24]. It was also localised using transcranial electrical and magnetic stimulation [25,26]. It is situated within the primary motor cortex between the arm and leg representations.…”
Section: The Cortical and Subcortical Respiratory Networkmentioning
confidence: 99%
“…Such studies suggest that the insula and operculum mediate dyspnea (Banzett et al, 2000;Evans et al, 2002;McKay et al, 2008;Peiffer, 2008;Peiffer et al, 2008;von Leupoldt et al, 2008), and the cingulate gyrus, the prefrontal cortex, and the supramarginal gyrus integrate emotional and sensory aspects of respiration. The motor cortex is implicated in the volitional control of breathing and speech (Gandevia and Rothwell, 1987;McKay et al, 2003;Brown et al, 2008). It is plausible that brain regions that express both high densities of opioid receptors and modulate respiration (particularly the insula, operculum, and prefrontal cortex) (Baumgärtner et al, 2006;Tracey and Mantyh, 2007) are likely to have a role in mediating opioid-induced respiratory depression.…”
Section: Introductionmentioning
confidence: 99%